ما بعد استشراق: معاصر مغرب میں مطالعہ اسلام - ڈاکٹر مستفیض احمد علوی (jihat-ul-islam, 2020)
The following paper explores the contemporary Western thinking and approaches to Islam and the Muslims, especially in the post-colonial period of EastWest binary relationship. The term Post-orientalism or Neo-orientalism may be used to explain post-modern or post-colonial manifestations of Western Orientalist thinking. Though it marks a change from classical Orientalism, the new phenomenon seems to be a supplement to enduring modes of Orientalist behavior. The classical Orientalists were European academicians, established writers and artists, whereas neo-Orientalists include armed forces officers and undercover agents like Sir Hamilton Alexander Rosskeen Gibb (1895–1971) and Bernard Lewis (born in 1916). The classic orientalist approach was reliant on a binary logic, and based on a claim of moral and cultural superiority over the Orient, whereas neo-orientalist attitude originates from Islamophobia; an intense fear or hatred against Islam and Muslims, taken as a geopolitical force. The post-orientalist phenomenon has introduced and produced several new narratives such as “the clash of civilizations,” the “war of ideas,” the “war on terror,” and “Islamo-fascism.”